Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Di Rsud Harjono Ponorogo - Nafi'Urrouf, Muhammad Habibie, Wahyuni, S.Fis,SKM, M.Kes (2015)
Background: (CTS) is a collection of symptoms due to compression of the median nerve in the carpal tunnel at the wrist, precisely under the flexor retinaculum. CTS is one of the diseases that are categorized as repetitive stress injuries, cumulative trauma disorder, overuse syndrome, or repetitive motion disorders. Disorders that arise in the CTS is caused by excessive use of hands to repeated stress and the twist of the wrist. Conditions often associated with CTS include pregnancy, inflammatory arthritis, Colles' fracture, amyloidosis, hypothyroidism and diabetes mellitus. Objective: To investigate the implementation of physiotherapy in reducing pain, tingling and tissue adhesions, provides sedative and relaxing effect improves blood circulation and increase the functional activity of the left hand on CTS cases with ultrasound modality and nerve mobilization. Results: After treatment for 6 times showed a decrease tenderness of T1 = value of 5 to T6 = value of 3 and painful movement, from T1 = value T6 grades 5 to 4, the increase in the value of the flexor muscle strength T1 = 4 becomes the value T6 = 4+, extensor muscle strength increase value T1 = 4 becomes the value T6 = 4+, decreasing tingling in the palms and fingers start of therapy 3 to 6 therapy. Conclusion: Ultrasound can reduce pain and tissue adhesions, provides sedative and relaxing effect improves blood circulation, nerve mobilization may reduce tingling nerve and can improve muscle strength.